2022
DOI: 10.2106/jbjs.oa.22.00023
|View full text |Cite
|
Sign up to set email alerts
|

ACL Reconstruction Patients Have Increased Risk of Knee Arthroplasty at 15 Years of Follow-up

Abstract: Background: Anterior cruciate ligament (ACL) injury is considered a risk factor for osteoarthritis. The primary aim of the present study was to investigate the cumulative risk of, and risk factors associated with, a subsequent knee arthroplasty after an ACL reconstruction at up to 15 years of follow-up. The secondary aim was to compare the relative risk of knee arthroplasty after ACL reconstruction compared with that in the general population. Methods: Data were analyzed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A possible explanation could be that the cartilage lesion increases the risk of knee arthroplasty substantially more than ACL and meniscal injury do, thereby limiting the functional impact of the latter. Visnes et al found a 3-times increased risk of knee arthroplasty in 30 to 39-year-old patients and a doubled risk in 40 to 49-year-old patients after ACL surgery compared with the general population 41 . In our cartilage cohort, the corresponding values were a 416-times increased risk and a 49-times increased risk, respectively.…”
Section: Risk Of Arthroplastymentioning
confidence: 99%
“…A possible explanation could be that the cartilage lesion increases the risk of knee arthroplasty substantially more than ACL and meniscal injury do, thereby limiting the functional impact of the latter. Visnes et al found a 3-times increased risk of knee arthroplasty in 30 to 39-year-old patients and a doubled risk in 40 to 49-year-old patients after ACL surgery compared with the general population 41 . In our cartilage cohort, the corresponding values were a 416-times increased risk and a 49-times increased risk, respectively.…”
Section: Risk Of Arthroplastymentioning
confidence: 99%
“… 2 , 3 Individuals who experience sports injuries are at risk of developing locomotory diseases. 3 , 4 Sports injuries adversely affect athletes in the present and the future because they affect athletes’ quality of life and longevity. Thus, sports injury prevention has become an important social issue from medical and public health perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent instability also results in downstream consequences, including further damage to structures essential for knee stability, as well as accelerated progression of osteoarthritis. 19 Multiple factors are responsible for the incidence of graft failure after ACLR. 2 , 13 Tunnel malposition of the femoral tunnel has been shown to be the cause of more than 80% of graft failures after ACLR.…”
mentioning
confidence: 99%